Cover, Content, and Editorial Note from Pengabdianmu J Pengabdian Masyarakat Vol. 4 No. 1 March 2019 - PengabdianMu J Pengabdian Masyarakat, Chief Editor of (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Assalamu’alaikum Wr. Wb. Dear reader, now PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat re-published on Volume 4 Issue 1 March 2019. The success of this publication is the result of good cooperation of all parties who maintain the publishing sustainability twice a year. Alhamdulillah, form this edition PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat has succeeded in gaining a proud achievement by successfully getting an accreditation rating on SINTA 4. This success cannot be separated from the support and prayer of all contributors, both material and non-material. The publication of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat certainly participates in disseminating the results of community services in science and technology development conducted by lecturers and researchers especially from UM Palangkaraya and other universities. This edition contains 11 articles consisting of Education, Social and Political, Islamic Studies, Engineering, and Health Science topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition in September 2019. Wassalamu’alaikum Wr. Wb. Palangka Raya, March 2019 Editor-in-Chief, signed Dr. Nurul Hikmah Kartini, S.Si., M.Pd.